Dissent and Diversity in Science and Technology Studies: Reply to Fuller, Kasavin and Shipovalova, and Turner. - Lynch, William T (Philosophy of the Social Sciences, 2022)
My argument in I Minority Report: Dissent and Diversity in Science i is that Imre Lakatos and Paul Feyerabend reconciled historicist and normative philosophy of science in ways that suggest a productive path forward for Science and Technology Studies (STS) and history and philosophy of science today. In that light, Kasavin and Shipovalova also question whether Lakatos is really a helpful guide when his approach seems to focus on the internal dynamic of scientific theories rather than a truly sociological approach. At the core of the difference between the philosophies of Lakatos and Feyerabend and that of Kuhn and his followers in STS is the emphasis on the existence throughout the history of science of multiple research programs rather than a single, hegemonic paradigm. Feyerabend rejected Lakatos' emphasis on research programs because he believed scientists were capable of hybridizing theories using the resources from distinct research programs.